2020
DOI: 10.31083/j.rcm.2020.01.5101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lipoprotein(a) on long-term outcomes after percutaneous coronary intervention in patients with reduced low-density lipoprotein cholesterol

Abstract: The purpose of this study is to investigate the effect of lipoprotein(a) level on long-range prognosis after Percutaneous Coronary Intervention (PCI) in patients with lowdensity lipoprotein cholesterol (LDL-C) goal attainment. In this retrospective study, 350 patients in Coronary artery disease (CAD) with LDL-C less than 1.8 mmol/L were enrolled in the Guangdong Institute of Cardiovascular Diseases from January 2011 to December 2013. Follow-up was 1 year after PCI. According to the median value of the study po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Most prior analyses on the risk for ASCVD events associated with lipoprotein(a) in adults with prevalent ASCVD were restricted to individuals who underwent a percutaneous coronary intervention at a single health care center or were taking a statin. 11 , 12 , 13 , 14 In a prior analysis of the UK Biobank, the age‐, sex‐, and race‐adjusted HR for CHD events associated with lipoprotein(a) ≥150 versus <150 nmol/L among UK adults with ASCVD was 1.23 (95% CI, 1.10–1.37). 16 However, most participants included in the analysis were White individuals, and results for those of other race were not reported separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most prior analyses on the risk for ASCVD events associated with lipoprotein(a) in adults with prevalent ASCVD were restricted to individuals who underwent a percutaneous coronary intervention at a single health care center or were taking a statin. 11 , 12 , 13 , 14 In a prior analysis of the UK Biobank, the age‐, sex‐, and race‐adjusted HR for CHD events associated with lipoprotein(a) ≥150 versus <150 nmol/L among UK adults with ASCVD was 1.23 (95% CI, 1.10–1.37). 16 However, most participants included in the analysis were White individuals, and results for those of other race were not reported separately.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 However, there are limited data about whether elevated lipoprotein(a) levels confer an increased risk for CHD and ischemic stroke events in individuals with ASCVD, particularly among Black adults, a population with higher lipoprotein(a) levels versus other racial groups. 9 , 10 , 11 , 12 , 13 , 14 If elevated lipoprotein(a) levels are associated with an increased risk for CHD and ischemic stroke events among Black and White adults with ASCVD, this would support the use of lipoprotein(a) for directing more intensive risk‐reduction interventions in this population.…”
mentioning
confidence: 99%
“…[51] High Lp(a) levels predict an increased incidence of revascularization, platelet aggregation, and thrombogenicity in Chinese patients with CAD after PCI. [52,53] Several studies have reported that plasma Lp(a) concentration and Lp(a) genetic variants are associated with long-term adverse cardiovascular events in patients with chronic kidney disease or CAD who underwent PCI, suggesting that Lp(a) measurements may be useful to stratify Chinese patients according to risk after PCI. [54][55][56][57][58][59][60] These findings may provide insight into future clinical applications of Lp(a).…”
Section: Atherosclerosismentioning
confidence: 99%
“…How are the effects of increased serum Lp(a) level on clinical outcomes in patients undergoing percutaneous coronary intervention (PCI) has been mainly evaluated in cohorts of Asian patients, with mixed results. While some studies suggested an increased risk for adverse clinical outcomes associated with elevated Lp(a) levels (12)(13)(14)(15), other studies failed to detect such an association (16,17). In the present study, we thus aimed to evaluate the clinical impact of Lp(a) in a large cohort of German patients undergoing percutaneous coronary intervention (PCI) with three-years of follow-up.…”
Section: Introductionmentioning
confidence: 97%